Radical mediated deoxygenation of inositol benzylidene acetals: conformational analysis, DFT calculations, and mechanism - Gurale, Bharat P.; Vanka, Kumar; Shashidhar, Mysore S. (Carbohydrate Research, 2012)
Xanthates of 1,3-benzylidene acetal derivatives of myo- and neo-inositols undergo dideoxygenation under Barton-McCombie conditions, as a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Scrutiny of structure of these bicyclic inositol derivatives shows that although the conformation of the two rings can vary depending on the configuration of the inositol ring and the phase in which the molecules are present, both the xanthates lead to the formation of the same dideoxyinositol. DFT calculations on these molecular systems suggest that neo-inositol derivatives undergo conformational change prior to radical formation while myo- inositol derivatives undergo conformational change subsequent to radical formation, during the deoxygenation reaction. A low barrier for intramolecular hydrogen transfer supports the extreme facility of this deoxygenation reaction. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Deoxygenation; DFT; Inositol; Mechanism; Radical; Xanthate

Reductive nitrosylation of nickel(II) complex by nitric oxide followed by nitrous oxide release - Ghosh, Somnath; Deka, Hemanta; Dangat, Yuvraj B.; Saha, Soumen; Gogoi, Kuldeep; Vanka, Kumar; Mondal, Biplab (Dalton Transactions, 2016)
Ni(II) complex of ligand L (L = bis(2-ethyl-4-methylimidazol-5-yl)methane) in methanol solution reacts with an equivalent amount of NO resulting in a corresponding Ni(I) complex. Adding further NO equivalent affords a Ni(I)-nitrosyl intermediate with the NiNO(10) configuration. This nitrosyl intermediate upon subsequent reaction with additional NO results in the release of N2O and formation of a Ni(II)-nitrito complex. Crystallographic characterization of the nitrito complex revealed a symmetric eta(2)-O,O-nitrito bonding to the metal ion. This study demonstrates the reductive nitrosylation of a Ni(II) center followed by N2O release in the presence of excess NO.

Role of the (104) MgCl2 lateral cut in ziegler-natta catalysis: a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (Journal of Physical Chemistry C, 2018)
Density functional theory (DFT) has been used for the study of ethylene polymerization in the Ziegler-Natta (ZN) olefin polymerization system for eight different alkoxy group containing titanium catalysts (Cat-A-h), Ti(III)Et(OR)(OR') (where R =-CH3,-Et,-tert-butyl, cyclohexane, R' = CH3,-Et,-tert-butyl, cyclohexane). What is of significance is that the catalysts studied were all considered to be tethered to the (104) MgCl2 surface, which has traditionally been considered a ``dormant'' surface in Z-N catalysis systems, in contrast to the ``more active'' (110) MgCl2 surface. Our calculations indicate that the binding of all the catalysts to the (104) surface is favorable, even after taking entropic effects into account. For purposes of comparison, ethylene polymerization has been investigated for the Cat-C (TiEt(OEt)(2)) and the Cat-H (TiEt(CI)(OC4H8Cl)) (OC4H8Cl = the chlorobutoxy group) cases, for both the (i) (110) and the (ii) (104) MgCl2 surfaces. It has been seen that for both (i) and (ii)-the energy gap between insertion and the termination barriers (Delta X) was nearly the same for both the Cat-C and Cat-H eases, which shows that ethylene polymerization on the (104)MgCl2 surface is likely to be a ptoininent occurrence in Z-N catalysis, when alkoxy groups are bound to the titanium center. Additionally, for the Cat-C and the Cat-H cases, the regio-and stereoselective behavior of the propylene monomer on the titanium species present on the (110) and the (104) MgCl2 surfaces has also been investigated, and the results indicate that the (104) MgCl2 surface is only slightly less effective than the (110. However, the calculations also indicate that for Cat-H the (104) MgCl2 surface significantly improves the molecular weight of polypropylene in comparison to the (110) surface, further showcasing how the (104) surface (ignored until date) might be a major player in ZN catalysis. Given that a major portion of the MgCl2 support is made up of (104) lateral cuts, the current findings are of considerable relevance.

Readily available lithium compounds as catalysts for the hydroboration of carbodiimides and esters - Bisai, Milan Kumar; Gour, Kritika; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Journal of Organometallic Chemistry, 2021)
Selective and efficient hydroboration of esters and carbodiimides to alcohols and amines by two welldefined and readily accessible lithium complexes, 2,6-di-tert-butyl phenolate lithium (1a ) and 1,1'-dilithioferrocene (1b ) are described. A range of aliphatic, aromatic, and cyclic esters with various functional groups were selectively converted into the corresponding boronate esters. Similarly, the single hydroboration of carbodiimides with aliphatic and aromatic substituents on the nitrogen atoms was studied. A possible mechanistic pathway of the hydroboration of carbodiimides with HBpin has been proposed using NMR studies and DFT calculations. These reactions are convenient alternatives to stoichiometric hydride reduction or hydrogenation. The employing of lithium complexes is also significant, because of the need to find cheap and green alternatives to noble metal complexes. (C) 2021 Elsevier B.V. All rights reserved.

Reactivity of four coordinate iridium complex towards hydrogen: an experimental and computational study - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Nethaji, Munirathinam; Jagirdar, Balaji R. (Journal of Organometallic Chemistry, 2022)
Reaction of a four coordinate, 16-electron Ir complex, [Ir-(iPr)4(POCOP)(PPh3)] (4 ) (((iPr)4)(POCOP= 2,6-bis(di-isopropyl phosphinito)benzene, kappa(3)-C6H3-1,3-[OP((iPr))(2)](2)), with H-2 resulted in an oxidative addition product, cis-dihydride complex, cis-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( cis-5 ) presumably via the intermediacy of a sigma complex, [Ir(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)]. The cis-dihydride complex completely isomerizes to the trans-dihydride complex trans-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( trans-5 ) under ambient conditions in about 3 h. It was found that the steric and electronic features on the iridium center have significant influence on the approach of H-2 onto the metal center followed by oxidative addition and isomerization. The isomerization process was studied in detail and all the mechanistic aspects have been elucidated using a combination of both experimental work and computation. The cis-dihydride complex isomerizes to the trans-dihydride by compensating the trans influence of the strongly trans-directing hydride ligand. A mechanism involving the exchange of the position of PPh3 with a hydride ligand cis to itself via PPh3 dissociation and re-coordination thereby resulting in the formation of the trans-dihydride complex, has been proposed for the isomerization. The cis-dihydride was found to be a highly active catalyst for hydrogenation of ethy-lene. A competing reactivity study of cis-dihydride between isomerization versus insertion of C2H4 into the Ir-H bond, was studied experimentally and computationally. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Insertion; iridium complex; isomerization; Oxidative addition; Reductive elimination

Room temperature chemoselective hydrogenation of C=C, C=O and C=N bonds by using a well-defined mixed donor Mn(I) pincer catalyst - Shabade, Anand B.; Sharma, Dipesh M.; Bajpai, Priyam; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Chemical Science, 2022)
Chemoselective hydrogenation of C=C, C=O and C=N bonds in alpha,beta-unsaturated ketones, aldehydes and imines is accomplished at room temperature (27 degrees C) using a well-defined Mn(I) catalyst and 5.0 bar H-2. Amongst the three mixed-donor Mn(I) complexes developed, kappa(3)-((PNNPyz)-P-R2-N-3)Mn(CO)(2)Br (R = Ph, Pr-i, Bu-t); the Bu-t -substituted complex ((PNNPyz)-P-tBu2-N-3)Mn(CO)(2)Br shows exceptional chemoselective catalytic reduction of unsaturated bonds. This hydrogenation protocol tolerates a range of highly susceptible functionalities, such as halides (-F, -Cl, -Br, and -I), alkoxy and hydroxy, including hydrogen-sensitive moieties like acetyl, nitrile, nitro, epoxide, and unconjugated alkenyl and alkynyl groups. Additionally, the disclosed method applies to indole, pyrrole, furan, thiophene, and pyridine-containing unsaturated ketones leading to the corresponding saturated ketones. The C=C bond is chemoselectively hydrogenated in alpha,beta-unsaturated ketones, while the aldehyde's C=O bond and imine's C=N bond are preferentially reduced over the C=C bond. A detailed mechanistic study highlighted the non-innocent behavior of the ligand in the ((PNNPyz)-P-tBu2-N-3) Mn(I) complex and indicated a metal-ligand cooperative catalytic pathway. The molecular hydrogen (H-2) acts as a hydride source, whereas MeOH provides a proton for hydrogenation. DFT energy calculations supported the facile progress of most catalytic steps, involving a crucial turnover-limiting H-2 activation.

Rivaroxaban eutectics with improved solubility, dissolution rates, bioavailability and stability - Shaligram, Parth S.; George, Christy P.; Sharma, Himanshu; Mahadik, Kakasaheb R.; Patil, Sharvil; Vanka, Kumar; Arulmozhi, S.; Gonnade, Rajesh G. (Crystengcomm, 2023)
Rivaroxaban (RXB) is a direct factor Xa inhibitor used for the treatment of deep vein thrombosis (DVT, a blood clot in the leg) and pulmonary embolism (PE, a blood clot in the lung) and to prevent blood clots in atrial fibrillation following hip or knee surgery. However, RXB suffers from poor solubility that hinders its broader application. Although its cocrystals are reported for solubility enhancement, the methodology used to prepare multi-component crystals is complex. Also, it uses hazardous solvents to develop cocrystals. We have prepared eutectics of RXB with caffeic acid (CAA), coumaric acid (CA), fumaric acid (FA), succinic acid (SA), mandelic acid (MA) and trimesic acid (TA) and analyzed them using hot stage microscopy (HSM), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and fourier transform infrared spectroscopy (FTIR) techniques. The saturation solubility and dissolution rate profiles were also obtained to investigate the effect of eutectics on these parameters. Amongst all the coformers tested, coformers CAA, CA, and FA showed significant enhancement in the solubility of RXB. The powder dissolution rate of the eutectics showed considerable enhancement compared to that of RXB. In vivo pharmacokinetic study was carried out for RXB-CAA, RXB-CA and RXB-FA in rats and compared with RXB, which showed 1.5 and 1.4 times enhancement in relative bioavailability for RXB-CAA and RXB-CA, respectively. Stability studies were carried out as per ICH guidelines for all the eutectics, which revealed excellent stability over six months under accelerated (40 degrees C and 75%) conditions and twelve months under long-term (30 degrees C and 60% RH) conditions. The DFT studies carried out using the B3LYP/TZVP level of theory revealed higher Gibbs free interaction energy (Delta G(int)) for homosynthons (drugMIDLINE HORIZONTAL ELLIPSISdrug and coformerMIDLINE HORIZONTAL ELLIPSIScoformer) than heterosynthons (drugMIDLINE HORIZONTAL ELLIPSIScoformer).

Rational monomer design for the synthesis of conjugated polymers by direct heteroarylation polymerization - Kakde, Navnath R.; Sharma, Himanshu; Dalvi, Nitin V.; Vanka, Kumar; Asha, S. K (ACS Polymers Au, 2024)
This study focuses on the design concepts that contribute to the C–H activation in bithiophene-flanked monomers incorporating naphthalene diimide (NDI), perylene diimide (PDI), and fluorene (FLU) and their polymerization by direct heteroarylation. Density functional theory (DFT) calculations reveal distinct energy requirements for C–H bond abstraction, which is dictated by the electron-withdrawing strength of the central aromatic core flanked by bithiophene. These provide insights into the reactivity of each monomer for C–H bond activation. Proton NMR spectroscopic experimental results confirm the favorable energetic profiles predicted by DFT, with NDI- and PDI-flanked monomers exhibiting lower energy requirements than fluorene-flanked monomers. Successful polymer synthesis is demonstrated for NDI and PDI, while the fluorene-flanked monomer shows challenges due to its higher energy demands.

Role of aromatic alcohol additives on asymmetric organocatalysis reactions: insights from theory - Banerjee, Subhrashis; Vanka, Kumar (Chemistry-an asian jounrnal, 2024)
The presence of an aromatic additive has been seen to enhance, often significantly, the enantioselectivity and yield in asymmetric organocatalysis. Considering their success across a dizzying range of organocatalysts and organic transformations, it would seem unlikely that a common principle exists for their functioning. However, the current investigations with DFT suggest a general principle: the phenolic additive sandwiches itself, through hydrogen bonding and pi & sdot;& sdot;& sdot;pi stacking, between the organocatalyst coordinated electrophile and nucleophile. This is seen for a wide range of experimentally reported systems. That such complex formation leads to enhanced stereoselectivity is then demonstrated for two cases: the cinchona alkaloid complex (BzCPD), catalysing thiocyanation (2-naphthol additive employed), as well as for L-pipecolicacid catalysing the asymmetric nitroaldol reaction with a range of nitro-substituted phenol additives. These findings, indicating that dual catalysis takes place when phenolic additives are employed, are likely to have a significant impact on the field of asymmetric organocatalysis. The current DFT based study, on a wide range of organocatalysis systems, reveals a general principle by which phenolic additives influence asymmetric organocatalysis reactions. It is shown that the phenolic additive forms a sandwich complex, through hydrogen bonding and pi & sdot;& sdot;& sdot;pi stacking interactions, with the organocatalyst coordinated electrophile and nucleophile, and enhances the enantioselectivity of the system as a result. image
Keywords: Additive; Asymmetric Organocatalysis; Cinchona Alkaloid; Density functional theory; Enantioselective Thiocyanation